Zinc restriction during different periods of life: Influence in renal and cardiovascular diseases - Tomat, Analia Lorena (2011)
Micronutrient undernutrition during critical periods of growth has become an important health issue in developing and developed countries, particularly among pregnant women and children having an imbalanced diet. Zinc is a widely studied microelement in infant feeding because it is a component of several enzymes involved in intermediary metabolism ranging from growth to cell differentiation and metabolism of proteins, carbohydrates, and lipids. Human and experimental studies have reported an association between zinc deficiency and the etiopathogenesis of cardiovascular and renal diseases like hypertension, atherosclerosis, congestive heart failure, coronary heart disease, and diabetes. The main links between the development of these pathologies and zinc deficiency are multiple mechanisms involving oxidative stress damage, apoptosis, and inflammation. A substantial body of evidence suggests that a poor in utero environment elicited by maternal dietary or placental insufficiency may " programme" susceptibility in the fetus to later development of cardiovascular, renal, metabolic, and endocrine diseases. Zinc deficiency in rats during intrauterine and postnatal growth can also be considered a model of fetal programming of cardiovascular and renal diseases in adult life. Dietary zinc restriction during fetal life, lactation, and/or postweaning induces an increase in arterial blood pressure and impairs renal function in adult life. This review focuses on the contributions of experimental and clinical studies to current knowledge of the physiologic role of zinc in the cardiovascular and renal systems. Moreover, this review examines the relationship between zinc deficiency during different periods of life and the development of cardiovascular and renal diseases in adult life. © 2011 Elsevier Inc.